Sensor Fusion and Fuzzy Logic for Stabilization System of Gimbal Camera on Hexacopter - Huda Ubaya; Hanipah Mawarni (ICON-CSE, 2014)
Hexacopter has the ability to fly in the air can be used as an air monitoring system. To get the video or images that have good quality then it is used gimbal camera as a movement stabilizer and vibration damping. Stabilization System consists of two axes, x axis (roll) and y axis (pitch) and has a 2-axis camera gimbal controller which is have microcontroller ATMEGA 328 that serves to regulate the stability of the gimbal camera. The Input of this system is derived from accelerometer and gyroscope sensors that are within the sensor module MPU 6050, to determine the tilt position of hexacopter. The output of this sensor will be filtered first using complementary filters that serve to reduce noise of both sensors and complement advantages and disadvantages of each sensor. The output of this system is the movement of two brushless motors, brushless roll and pitch, that are controlled with Sugeno fuzzy logic method because it has a simple calculation so the response is faster and more suitable for real-time applications. From the case study with the data of the roll at by 35 º and pitch at by 17 º resulting PWM duty cycle value by -69.47% roll and pitch resulting PWM duty cycle value by -25.5 %, where (-) represents the direction of movement.